Sperm characteristics, antioxidant status and hormonal profile in rats treated with artemisinin (2013)
The indiscriminate use, abuse and patients’ noncompliance to normal prescription of artemisinin and its derivatives are a common practice during the treatment for drug-resistant malaria parasites in most developing countries. This study investigated the influence of artemisinin on the testicular and epididymal sperm antioxidant systems as well as on the plasma levels of hormones from the pituitary and thyroid components of the brain–pituitary–testicular axis. Oral exposure of rats to 0, 7 and 35 mg kg_1 artemisinin for 7 days showed that the testicular antioxidant status at both therapeutic dose (7 mg kg_1) and overdose (35 mg kg_1), and the sperm antioxidant status at therapeutic dose of artemisinin remained unaffected compared with control. However, increased hydrogen peroxide and lipid peroxidation levels were accompanied by a concomitant decrease in glutathione peroxidase and glutathione-S-transferase activities as well as glutathione level in spermatozoon of rats administered with overdose of artemisinin. While plasma levels of all the hormones investigated remained unaffected, severe epididymal degeneration with concomitant decrease in sperm quantity and quality was observed in rats treated with overdose of artemisinin compared with control. Overall, induction of oxidative stress in the epididymis, but not in the testes, could cause reproductive deficits in individuals unduly undergoing artemisinin therapy.